2022
DOI: 10.1021/acs.langmuir.2c01389
|View full text |Cite
|
Sign up to set email alerts
|

Optical Chemosensors based on Spiropyran-Doped Polymer Nanoparticles for Sensing pH of Aqueous Media

Abstract: Photochromic polymers, which are prepared by the incorporation of photochromic compounds into polymer matrices, show fluorescence emission along with color change under UV light irradiation. Polymer nanoparticles yield high chromic properties at low chromophore loadings, as they have a large surface area to absorb a high level of light irradiation. Particle size is a significant parameter to control optical properties, where the decrease of particle size results in a high light absorption and efficiency of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…As an application of the emulsion, photochromism was investigated. Photochromism which is a phenomenon of photocoloration and thermal- (or photo-) decoloration, is useful phenomena for optical recording and smart materials . The emulsion containing the photochromic molecule was red, and the color faded out by visible light irradiation, as shown in Figure b, showing the negative photochromism.…”
Section: Resultsmentioning
confidence: 99%
“…As an application of the emulsion, photochromism was investigated. Photochromism which is a phenomenon of photocoloration and thermal- (or photo-) decoloration, is useful phenomena for optical recording and smart materials . The emulsion containing the photochromic molecule was red, and the color faded out by visible light irradiation, as shown in Figure b, showing the negative photochromism.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the same authors reported the fabrication of photochromic polymer nanoparticles doped with spiropyran for pH sensing. [ 98 ] It was found that the optical properties could be affected by media’ pH and copolymer composition, thus, based on the colorimetric and fluorescence detection mechanisms, the potential application of photochromic polymer nanoparticles as optical pH chemical sensors could be realized.…”
Section: Applications Of Fluorescent Polymer Particlesmentioning
confidence: 99%
“…[97] In the work published by Roghani-Mamaqani and coworkers, photochromic polymer nanoparticles doped with spiropyran were prepared by nanoprecipitation and served as optical pH chemosensors. [98] Specifically, PMMA homopolymer and its two copolymers were synthesized by reverse atom transfer radical polymerization (RATRP). It should be pointed out that RATRP could not only control the molecular weight of the polymers, but also overcome the catalyst' oxidation, as well as generate different charges on the surface of the subsequently prepared photochromic nanoparticles.…”
Section: Nanoprecipitationmentioning
confidence: 99%
“…2,4 Variation of ionic strength and pH of media can alter the photochromism properties and fluorescence emission of the nanoparticles, which can be used in pH sensing applications. [23][24][25][26][27] Paek et al prepared polymer-quantum dot nanoparticles which respond to acidic range of pH variations. The results indicated that the color and fluorescence emission of the samples change under different acidic pHs.…”
Section: Introductionmentioning
confidence: 99%